MODERASI AUDITOR PROFESSIONAL SCEPTICISMPADA KOMPLEKSITAS TUGAS AUDIT, LOCUS OF CONTROLDAN KUALITAS AUDIT - Aziza, Nurna; Agus, Andi; Hastina, Safira (Yayasan Nuraini Ibrahim Mandiri, 2024)
Audit quality is the result achieved from financial statements that are presented fairly, all material matters or provide a true picture according to the financial reporting framework in order to increase the trust of users of financial statements. The purpose of this study is to investigate whether the complexity of the audit task, and locus of control can affect audit quality and auditor professional scepticism can moderate the effect of audit task complexity, and locus of control on audit quality. Type of research is quantitative research, in this study the data collection method is the distribution of questionnaires via g-form. The data collected in this study are the results of questionnaires distributed to auditors at public accounting firms in Indonesia. The results of this study audit task complexity and locus of control have a positive effect on audit quality, auditor professional scepticism cannot moderate the effect of audit task complexity and locus of control on audit quality.Keyword: Audit Quality, Audit Task Complexity, Locus of Control, and AuditorProfessional Scepticism.